Acute oral toxicity from afFraction rich in phenolic compounds from the leaf extract of Swietenia macrophylla king in a murine model - HENAO DUQUE, Ana María; RODRÍGUEZ, Berardo de Jesús; PEREAÑEZ, Jaime Andrés; LOBO-ECHEVERRI, Tatiana; NÚÑEZ RANGEL, Vitelbina (Vitae, 2017)
Background: The mahogany tree (Swietenia macrophylla King) is widely used in traditional medicine, especially its seeds, which are used in Malaysia, Indonesia and some countries of South America. Recently an active fraction of the leaf ethanolic extract (labelled “Sm13-16,23”), showed promising results against some toxins of South American pit vipers. Objective: In this study the aim was to evaluate the acute oral toxicity of fraction Sm13-16,23 from the leaf ethanolic extract, using Swiss Webster mice. Materials and Methods: Fraction Sm13-16,23 was administered orally in a single dose to 2000 mg/kg and 300 mg/kg, clinical follow-up for 14 days was performed and then euthanasia, necropsy and histopathology of organs were performed. Results: Overall, there were not deaths recorded during the study period. Further not signs of toxicity in doses of 300mg/Kg were observed, but at doses of 2000 mg/kg, histopathological lesions in the liver, as karyomegaly and the binucleation were observed. Conclusion: Fraction Sm13-16,23 does not produce toxicity lesion at doses of 300mg/kg, indicating that the acute oral toxicity risk is low.